The Development of Problem-Based Learning Liveworksheets to Improve Mathematical Communication Skills on Junior High School Students - Nurjiah, Tia; Minarti, Eva Dwi; Fitiranna, Aflich Yusnita (IKIP Siliwangi, 2024)
Communication skill is an ability that needs to be possessed by students. Through communication, students can express their opinions or ideas to their friends or to the teacher. The facts in the field show that students' mathematical communication skills are in the low category, therefore a solution is needed to improve students' mathematical communication skills. This research aims to produce problem-based learning-based LKPD assisted by liveworksheets to hone students' mathematical communication skills. This research was conducted at SMPN 1 Ngamprah. The subjects of this study amounted to 10 students on a limited trial. 34 students for a broad trial. The method used is development research according to Sugiyono which is modified into 7 stages carried out due to time constraints, namely: potential and problems, data collection, product design, design validation, design revision, product trial, and product revision. Data collection tools for this study are validation sheets, student response questionnaires, and 5 questions about mathematical communication skills in statistics material. Based on the results of value processing from validators, it shows that the developed LKPD is said to be suitable for use in learning, with an average percentage of assessment from validators of 85%. The results of the calculation of student answers show that the developed LKPD is effective for improving mathematical communication skills, with an average calculation of each indicator of 72.35%. It can be concluded that problem-based learning-based LKPD assisted by liveworksheets can be used in learning as an effort to improve students' mathematical abilities in statistics material.